Novos dados sobre a paisagem urbana da Santarém medieval (séculos V-XII): a necrópole visigoda e islâmica de Alporão - Marco Liberato (Medievalista)
Crossing the data collected during a archaeological intervention in the numbers 5 to 8, Rua Cinco de Outubro, in Santarém with some written sources, we present a proposal around the medieval urban landscape of the city during the centuries prior to their integration in the christian orbit and in the moments immediately following to the conquest of 1147. In this preliminary approach we intend to enable the relevance of using the increasing volume of information from the archaeological activity as a fundamental source to clarify some doubts and test current and new hypotheses related with the evolution of the cadastre in the medieval city